Perception of feasibility and social new ventures success: an exploratory study - Bernardino, Susana (2018)
This research aims to understand the role that individuals’ perception about the feasibility of a social venture plays on the decision to initiate a social project in Portugal and the extent to which individuals’ skills and abilities shape their perceptions. To attain this goal, a survey was undertaken among a sample of individuals responsible for the creation of Portuguese social ventures. The results showed that the perception of the feasibility of the social venture is closely related to individuals’ required skills/abilities and the desirability of the initiative. Specifically, it seems critical that the social value produced by the project will be fairly appreciated by the society and the target audience (donors, beneficiaries). For older people and individuals with no previous entrepreneurial and managerial experience, institutional support that increases external environment favorability is also considered important.